The Effect Of Banking Reputation And Teller Services On Customer Satisfaction At Regional Development Banks South Sulawesi Main Branch Mamuju - Novita , Ni Made; S , Ramli; Junaeda , Junaeda (Jurnal Economic Resource, 2024)
The Regional Development Bank of South Sulawesi, Mamuju Main Branch always strives to improve teller services in providing satisfaction to customers. The teller work unit of the Regional Development Bank of South Sulawesi, Mamuju Main Branch is the spearhead that will shape the company's image and deal directly with customers, the teller position is in the front liners position such as teller staff. This study uses banking reputation and teller services as independent variables and customer satisfaction as dependent variables, sampling using slovin with 100 customers, the test tools used are validity test, reliability test and multiple linear regression test or partially with a significant degree of 0.05 ( e = 5%). From the results of the t test in the table, the calculated t value of the banking reputation variable (X1) is 7.082 while the t table value is 1.66105 with a significant value of 0.000 <0.05. So Ha is accepted and Ho is rejected. Teller service (X2) is 5.224 while the t table value is 1.66105 with a significant value of 0.004 <0.05. So it can be seen that the calculated t > t table, so Ha is accepted and Ho is rejected. The results of the simultaneous test show that the F count value is 9.553 > F table 2.70 with a significant level of 0.000 < 0.05, so the regression model explains that banking reputation and teller services together have a significant effect on customer satisfaction at the Development Bank South Sulawesi area, Mamuju Main Branch